Hubungan antara Inovasi Kepala Madrasah dengan Tingkat Kesejahteraan Guru Madrasah Tsanawiyah se-Kecamatan Dua Boccoe Kabupaten Bone - A. Nurul Ikhsana; St. Syamsudduha; M. Yusuf Tahir (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2021)
This article discusses the relationship between innovation in madrasah principals and the welfare level of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency. This type of research is classified as quantitative (correlational) research with methodological (positivistic-quantitative) and scientific (sociological and psychological) approaches. The population in this study were 77 teachers taken from all existing teachers at Madrasah Tsanawiyah in Dua Boccoe District, Bone Regency. The data collection technique used was a questionnaire, while the analysis thechique used was descriptive analysis with hypothesis testing using product moment correlation analysis. The results of the study were: 1) the reality of the innovation ability of Madrasah Tsanawiyah principals in Dua Boccoe District in the very good category with a percentage of 62.33%; 2) the reality of the welfare level of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency is in the very good category with a percentage of 67.53%; 3) there is a correlation between the principal’s ability to innovate and the welfare of Madrasah Tsanawiyah teachers in Dua Boccoe District, Bone Regency. Evidenced by the correlation coefficient velue of correlation and is in the interval 0.40-0.599.